Forced vibration analysis of a fibre-reinforced polymer laminated beam using the green function method - Li, Xuan; Halim, Dunant; Liu, Xiaoling (2020)
This work aims to study forced vibration characteristics of Fibre-Reinforced Polymer (FRP) composite laminated beam with different properties, through a development of an analytical model using the Green function method. The forced vibration characteristics of a FRP laminated beam structure is generally more complex than those of a homogeneous beam structure since each layer is anisotropic with a different layer having different properties. In this work, the Green function method is used to model an FRP laminated beam to solve the associated equation of motion. The proposed analytical model allows a more efficient parametric analysis to be done on FRP laminated beams, in contrast to using a numerical model that is more computationally expensive. The analytical model is verified through a comparison with the numerical model of FRP laminated beam. Based on the developed model, a FRP laminated beam with various fibre orientations, is studied under forced vibration, demonstrating the effectiveness of the proposed method for forced vibration analysis of a laminated beam.